STATISTICAL ANALYSIS OF CHARACTERISTIC FEATURE VALUES IN IMAGE RECOGNITION - Gorokhovatsky, V. A.; Kuzmin, S. V. (Radio Electronics, Computer Science, Control, 2024)
Results of researches on application of the statistical approach are resulted at formation, an estimation of values, the analysis of properties and an establishment of equivalence of characteristic attributes of images with a view of structural recognition of objects. Experimental estimations confirm an opportunity of construction of optimum local decisions.